2019
DOI: 10.1016/j.celrep.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

ATGL/CGI-58-Dependent Hydrolysis of a Lipid Storage Pool in Murine Enterocytes

Abstract: Summary As circulating lipid levels are balanced by the rate of lipoprotein release and clearance from the plasma, lipid absorption in the small intestine critically contributes to the maintenance of whole-body lipid homeostasis. Within enterocytes, excessive triglycerides are transiently stored as cytosolic lipid droplets (cLDs), and their mobilization sustains lipid supply during interprandial periods. Using mice lacking adipose triglyceride lipase (ATGL) and its coactivator comparative gene ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 51 publications
5
52
0
Order By: Relevance
“…As we have reliably enriched ATGL from other cells and tissues employing the same activity-based approach, this finding indicates low expression levels and/or activity of ATGL in the small intestine. This is in line with recent results showing that ATGL/ABHD5 deletion does not affect luminal lipid absorption or CM secretion of enterocytes ( 14 ). Despite its significant enrichment in jejunum and ileum, HSL has already been ruled out as a bulk TAG hydrolase in enterocytes ( 13 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As we have reliably enriched ATGL from other cells and tissues employing the same activity-based approach, this finding indicates low expression levels and/or activity of ATGL in the small intestine. This is in line with recent results showing that ATGL/ABHD5 deletion does not affect luminal lipid absorption or CM secretion of enterocytes ( 14 ). Despite its significant enrichment in jejunum and ileum, HSL has already been ruled out as a bulk TAG hydrolase in enterocytes ( 13 ).…”
Section: Discussionsupporting
confidence: 93%
“…A recent study utilizing intestine specific double knock-out mice lacking both, ATGL and its activator alpha/beta hydrolase domain-containing protein 5 (ABHD5 alias CGI-58, Q9DBL9, Abhd5), showed prominent accumulation of TAG in the proximal parts of the small intestine 14 . However, the same study revealed that this TAG originates from the basolateral side of the enterocyte and not from dietary lipids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if ATGL plays an important role in the hepatic lipid droplet degradation, the degraded triglycerides seem to be channelled towards fatty acid oxidation rather than VLDL-dependent triglyceride secretion [62,63]. Interestingly, in the intestine, ABHD5 and ATGL also participate in lipid droplet degradation but not in chylomicron synthesis as their double knockout in the small intestine of mice does not affect plasma triglyceride levels [66]. Our results confirmed the role of ATGL in lipid droplet degradation in liverderived cells.…”
Section: Plos Pathogenssupporting
confidence: 77%
“…Mice were sacrificed 4 h post-gavage and lipid concentrations in duodenum, jejunum, and ileum were estimated [ 18 ]. Histologic sections of the small intestine and oil red O (ORO) staining were performed as described [ 19 ].…”
Section: Methodsmentioning
confidence: 99%